I'adah Friday Prayer with Zuhur Prayer in Syafi'iyyah Fiqh Perspective (Case Study at Al-Amin Mosque Meurah Village, Samalanga District, Bireuen Regency) - Syamsul Bahri; Safrizal Safrizal; Rahmiyati Rahmiyati (Budapest International Research and Critics University, 2021)
This study is to examine how the determination of Friday prayers and the midday prayer in Syafiiyah fiqh, the factors that cause Friday prayers to be mandatory with noon prayers at the Meurah mosque, the causes of differences in the practice of Friday prayers and midday prayers in meurah mosque. And find differences between the congregation who perform I'adah and those who do not perform I'adah in accordance with the concept of syafiiyyah fiqh. This research is a field research using descriptive qualitative research methods. The author uses an empirical or sociological (empirical or sociological) approach. The population is men who are mature and live in the village of Meurah who carry out Friday worship at the Al-Amin Mosque, Samalanga District, Bireuen Regency, Aceh. The results of the study found the law of Friday prayer with noon because Friday experts are not up to 40 people in Syafi'iyyah fiqh, there are three laws, the first is obligatory to pray, forbidden to pray, and circumcised i'adah. The implementation of the Friday prayer with noon performed by the congregation at the Al-Amin Meurah mosque, Samalanga district, Bireun district, because Friday experts were less than 40 worshipers. Friday congregations who perform Friday I'adah with noon because they believe they will not be appointed Friday because the number of Friday members is not up to 40 people. Friday with noon.